Времена года: стихотворения, рассказы, сказки, загадки / ред. М. Калугина - Калугина М. (Внеклассное чтение, 2008)
Экземпляры: ф.7 (2008) / Инвентарный номер: 52344 / Цена: / Сис.шифр: 84(2Рос=Рус) / Авт.знак: В 81 / ГРНТИ: 17.82.93 / ББК: 84(2Рос=Рус)